Yap1-mediated Flr1 expression reveals crosstalk between oxidative stress signaling and caffeine resistance in Saccharomyces cerevisiae - Choi, Ji Eun; Heo, Seo-Hee; Chung, Woo-Hyun (Frontiers in Microbiology, 2022)
Caffeine, a methylxanthine derivative, affects various physiological conditions such as cell growth, proliferation, and energy metabolism. A genome-wide screening for genes required for caffeine resistance in Schizosaccharomyces pombe revealed several candidates, including Pap1 and downstream target genes involved in caffeine efflux. We found that Yap1, a budding yeast AP-1 homolog required for oxidative stress response, has a caffeine tolerance function. Although the yap1 mutant is not sensitive to caffeine, overexpression of Yap1 renders cells resistant to high concentrations of caffeine. Caffeine sensitivity of mutants lacking two multidrug transporters, Pdr5 or Snq2, is completely recovered by Yap1 overexpression. Among Yap1-dependent target genes, FLR1, a fluconazole-resistant gene, is necessary but not sufficient for caffeine tolerance. Low concentrations of hydrogen peroxide induce Yap1 activation, which restores cell viability against caffeine toxicity. Intriguingly, oxidative stress-mediated cellular adaptation to caffeine toxicity requires Yap1, but not Flr1. Moreover, caffeine is involved in reduction of intracellular reactive oxygen species (ROS), as well as mutation rate and Rad52 foci formation. Altogether, we identified novel reciprocal crosstalk between ROS signaling and caffeine resistance.